Presynaptic GABAB Receptor Regulates Activity-Dependent Maturation and Patterning of Inhibitory Synapses through Dynamic Allocation of Synaptic Vesicles - Fu, Yu; Wu, Xiaoyun; Lu, Jiangteng; Huang, Josh (Frontiers in Cellular Neuroscience, 2012)
Accumulating evidence indicate that GABA regulates activity-dependent development of inhibitory synapses in the vertebrate brain, but the underlying mechanisms remain unclear. Here we combined live imaging of cortical GABAergic axons with single cell genetic manipulation to dissect the role of presynaptic GABAB receptors (GABABRs) in inhibitory synapse formation in mouse. Developing GABAergic axons form a significant number of transient boutons but only a subset was stabilized. Synaptic vesicles in these nascent boutons are often highly mobile in the course of tens of minutes. Activation of presynaptic GABABRs stabilized mobile vesicles in nascent boutons through the local enhancement of actin polymerization. Inactivation of GABABRs in developing basket interneurons resulted in aberrant pattern of bouton size distribution, reduced bouton density and reduced axon branching, as well as reduced frequency of miniature inhibitory currents in postsynaptic pyramidal neurons. These results suggest that GABABRs along developing inhibitory axons act as a local sensor of GABA release and promote presynaptic maturation through increased recruitment of mobile vesicle pools. Such release-dependent validation and maturation of nascent terminals is well suited to sculpt the pattern of synapse formation and distribution along axon branches.